Adiabatically prepared spin‐lock approach for T1ρ‐based dynamic glucose enhanced MRI at ultrahigh fields. Issue 1 (13th August 2016) - Schuenke, Patrick; Koehler, Christina; Korzowski, Andreas; Windschuh, Johannes; Bachert, Peter; Ladd, Mark E.; Mundiyanapurath, Sibu; Paech, Daniel; Bickelhaupt, Sebastian; Bonekamp, David; Schlemmer, Heinz‐Peter; Radbruch, Alexander; et al.
Abstract : Purpose: Chemical exchange sensitive spin‐lock and related techniques allow to observe the uptake of administered D‐glucose in vivo. The exchange‐weighting increases with the magnetic field strength, but inhomogeneities in the radiofrequency (RF) field at ultrahigh field whole‐body scanners lead to artifacts in conventional spin‐lock experiments. Thus, our aim was the development of an adiabatically prepared T1ρ ‐based imaging sequence applicable to studies of glucose metabolism in tumor patients at ultrahigh field strengths. Methods: An adiabatically prepared on‐resonant spin‐lock approach was realized at a 7 Tesla whole‐body scanner and compared with conventional spin‐lock. The insensitivity to RF field inhomogeneities as well as the chemical exchange sensitivity of the approach was investigated in simulations, model solutions and in the human brain. Results: The suggested spin‐lock approach was shown to be feasible for in vivo application at ultrahigh field whole‐body scanners and showed substantially improved image quality compared with conventional spin‐lock. The sensitivity of the presented method to glucose was verified in model solutions and a glucose contrast was observed in a glioblastoma patient after intravenous administration of glucose solution. Conclusion: An adiabatically prepared spin‐lock preparation was presented that enables a homogeneous and chemical exchange sensitive T1ρ ‐based imaging at ultra‐high field whole‐body scanners, e.g., for T1ρ ‐based dynamic glucose enhanced MRI. Magn Reson Med 78:215–225, 2017. © 2016 International Society for Magnetic Resonance in Medicine